Some Australian Reflections on Roncarelli v. Duplessis - Aronson, Mark (McGill Law Journal / Revue de droit de McGill, 2010)
Roncarelli v. Duplessis figures far more frequently in Australia’s secondary literature than in its court decisions, and it is noted not for its invalidation of Prime Minister Duplessis’s actions, but for its award of damages where judicial declaration of invalidity would usually be the only remedy. Invalidating Duplessis’s interference with Roncarelli’s liquor licence would have been the easy part of the case had it been tried in Australia. Australian statutes afforded good protection to liquor licensees, and general administrative law principles confined seemingly unfettered discretionary powers in less solicitous statutory regimes. In addition, the constitutional abolition of internal trade barriers used to be taken as banning unfettered regulatory powers over interstate traders.Duplessis’s tort liability was the hard part. His assumption of legal power was not deliberate, but it was extraordinarily indifferent to questions of legality. Justice Rand characterized this as “malice”, which in turn triggered liability to a uniquely public law tort known nowadays as misfeasance in public office. That tort is likely to cover more forms of non-deliberate official misconduct in Canada than in Australia, whose High Court usually avoids open-ended legal principles, particularly those according immediate operative force to substantive conceptions of the rule of law.